Non-Circular Journal Bearings - Chauhan, Amit (SpringerBriefs in Materials,, 2016)
This brief details non-circular journal bearing configurations. The author describes the mathematical and experimental studies that pertain to non-circular journal bearing profiles and how they can be applied to other types of bearing profiles with some modifications. He also examines non-circular journal bearing classifications, the methodology needed to carry out mathematical modeling, and the experimental procedures used to determine oil-film temperature and pressures.